A case report of dengue hemorrhagic fever complicated with diabetic ketoacidosis in a child: challenges in clinical management - V. Thadchanamoorthy; Kavinda Dayasiri (BMC, 2020)
Abstract Background Diabetic ketoacidosis (DKA) is a common presentation of type 1 diabetes mellitus (T1DM) precipitated by various bacterial and viral infections. Dengue infection is no exception for this and can be a precipitating factor for DKA. The presentation of DKA with dengue haemorrhagic fever (DHF) has been reported in adults. However, it is very rarely observed in children. Case presentation We present the case of a paediatric patient who was previously healthy and subsequently, developed polyuria (above 3 ml/kg/hour), irritability and high blood glucose (724 mg/dl) during the critical phase of DHF. DKA was diagnosed with DHF and managed successfully with insulin and intravenous fluids. He recovered without complications and discharged home with follow up being arranged at the endocrinology clinic. Conclusions When both DHF and DKA present together in a patient, meticulous monitoring of glycaemic control as well as fluid management is required to reduce the potential risk for severe complications of both conditions. Since there are no similar paediatric case reported in the literature, this case report might inspire paediatricians to anticipate the possibility of DKA in children with DHF.